OPTIMALISASI BURSA KERJA KHUSUS DI SMK NEGERI 2 BUDURAN UNTUK MENINGKATKAN PENYERAPAN LULUSAN KE DUNIA KERJA - Dimas Dimas Maldini; Eni Rustianingsih (Halu Oleo University, 2025)
This study aims to analyse and describe the optimisation of the Special Job Market of SMK Negeri 2 Buduran in increasing the absorption of graduates into the workforce. The method used is a descriptive qualitative approach, with data collection through interviews, observations, and documentation. The analysis focused on five optimisation indicators according to Agus Dwiyanto, namely Productivity, Service Quality, Responsiveness, Responsibility, and Accountability. The results of the study indicate that the Performance of BKK SMK Negeri 2 Buduran can be said to be quite good, but can still be improved in its optimisation. This is caused by the lack of existing Resources in BKK and also Partners regarding skills and skills training. This study concludes that the optimisation of Special Job Exchanges can be increased effectively by taking into account the capabilities and quantity of Human Resources, and also Cooperation with Partners who oversee skills training. These efforts are needed to improve the quality of graduates who have good competencies and can compete.